Anti-Melanogenic Activity and Cytotoxicity of Pistacia vera Hull on Human Melanoma SKMEL-3 Cells - Parisa Sarkhail; Mona Salimi; Pantea Sarkheil; Hirsa Mostafapour Kandelous (Acta Medica Iranica, 2017)
Pistacia vera seed is a common food and medicinal seed in Iran. It's hull (outer skin) as a significant byproduct of pistachio, is traditionally used as tonic, sedative and antidiarrheal and has been shown to be a rich source of antioxidants. The aim of the present study is to evaluate the anti-melanogenic activity of the pistachio hulls in order to discover a new alternative herbal agent to treat skin hyperpigmentation disorders. In this work, antioxidant and anti-tyrosinase activity of MeOH extract from Pistacia vera hull (MPH) were evaluated in vitro, respectively, by DPPH radical scavenging and mushroom tyrosinase activity assays. Then the effect of MPH on the melanin content, cellular tyrosinase activity and cytotoxicity (MTT assay) on human melanoma SKMEL-3 cell were determined followed by 72 h incubation. The results indicated that MPH had valuable DPPH radical scavenging effect and weak anti-tyrosinase activity when compared to the well-known antioxidant (BHT) and tyrosinase inhibitor (kojic acid), respectively. MPH, at a high dose (0.5 mg/mL), showed significant cytotoxic activity (~63%) and strong anti-melanogenic effect (~57%) on SKMEL-3 cells. The effect of MPH in the reduction of melanin content may be related to its cytotoxicity. The results obtained suggest that MPH can be used as an effective agent in the treatment of some skin hyperpigmentation disorders such as melanoma.